Connectivity Algorithm in Simple Graphs - Reza Wafdan; Mahyus Ihsan; Rahmah Zuhra (Jurnal Natural, 2014)
This paper discusses about connectivity algorithm in simple graphs. The algorithm has three stages, namely, adjacent vertices search, adjacent vertices investigation and component investigation. The aim of connectivity algorithm is to check whether a graph is connected or disconnected with the scope set. There are three sets which are used in this algorithm, namely, vertex, edge and adjacent vertices sets. The simple graph is connected if the graph has only one component or if the number of adjacent vertices elements is equal to the number of vertices. Otherwise, if the simple graph has more than one component or if the number of adjacent vertices elements is not equal to the number of vertices then the algorithm will conclude that the graph is disconnected.